VALIDASI METODE KROMATOGRAFI LAPIS TIPIS (KLT)-DENSITOMETRI UNTUK PENETAPAN KADAR Î²-KAROTEN DALAM TABLET KUNYAH EKSTRAK Spirulina platensis - Siti Fatmawati Fatimah; Citra Ariani Edityaningrum; Wihasty Nur Istyqomah; Ibnu Gholib Gandjar; Laela Hayu Nurani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Analytical Validation Method to determine Î²-carotene in the Spirulina platensis extract chewable tablets need to be done to ensure the quality. The purpose of this study is to prove the validity of the TLC-Densitometry method for determining the levels of Î²-carotene in the Spirulina platensis extract chewable tablets. Validation of the analysis method was carried out using standard Î²-carotene and spirulina chewable tablets in ethyl acetate solvents including specificity, linearity, repeatability precision, intermediate precision, limit of detection and limit of quantitation with stationary phase of silica gel 60 F254 and mobile phase of acetone: ethyl acetate (1: 1 v/v) using the TLC method, then quantitative analysis was carried out with a Densitometer at a wavelength of 453 nm. The results showed that the TLC-Densitometry method was linear with an r value of = 0.9938, having a repeatability precision with RSD 1.89%, intermediate precision with an RSD value of 2.401%, an LOD of 0.159 mg/mL and an LOQ of 0.531 mg/mL, and the specificity showed that this method is not specific to Î²-carotene compounds and the accuracy does not indicate a recovery value. Based on these results it can be concluded that the TLC-densitometry method is invalid for the determination of Î²-carotene levels in the Spirulina platensis extract chewable tablets.